The Policy Power of the Westminster Parliament: The "Parliamentary State" and the Empirical Evidence. Issue 1 (28th April 2015) - Russell, Meg; Cowley, Philip
Abstract : Drawing on several large research projects, and using both quantitative and qualitative evidence, this article assesses the policy influence of the Westminster parliament. Frequently dismissed as powerless in both academic and more popular accounts, we instead show evidence of an institution with significant policy influence, at successive stages of the policy process. Conventional accounts have focused too much on the decision‐making stage, to the exclusion of parliament's role at earlier and later policy stages. Critics have also focused disproportionately on visible influence, overlooking behind‐the‐scenes negotiations and the role of anticipated reactions. Based on analysis of over 6, 000 parliamentary votes, 4, 000 legislative amendments, 1, 000 committee recommendations, and 500 interviews, we conclude that Westminster's influence is both substantial and probably rising.